The Formation Of A False Positive Sexual Abuse Due To Thrombocytopenia: A Case Report - Polater, Erdogan; Bütün, Celal; Ekici, Mahmut; Sari, Seda Aybuke (The Bulletin of Legal Medicine, 2021)
Child abuse is a serious problem with tragic consequences, including medical, legal, developmental and psychosocial. Child sexual abuse is the most difficult to detect among child abuse types. It is an important public health problem that has been faced with serious difficulties in diagnosing and has not been appeared the greater part of it. Our case is about a two-years three-month-old girl. The patient was chosen as a case after evaluating suspected child abuse and haemolytic uremic syndrome, finding such as subcutaneous bleeding, and sexual abuse which is based on thrombocytopenic ecchymosis. Within importance of diagnosing findings of abuse, some diseases or lesions should be evaluated well in the differential diagnosis. In this study, it was aimed to draw attention to a case report that it is necessary to consider hematologic, gastrointestinal and some infectious diseases in the differential diagnosis of findings that evaluate false positive as sexual abuse.
Keywords: Hemolytic uremic syndrome; Thrombocytopenia; Sexuel abuse; Forensic medecine